2010
DOI: 10.4103/0973-1229.58823
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of Autism and Seizures: Understanding Cognitive Comorbidity

Abstract: This article introduces the concept of ‘cognitive comorbidity,’ which lays emphasis on common cognitive deficits that cut across different disorders. The concept is illustrated with the help of two commonly reported overlapping conditions (autism and epilepsy). It is further explained by concentrating on two important cognitive processes of facial emotional recognition and emotional memory, shown to be compromised in both conditions; and their underlying neural substrates. Cognitive comorbidity is then contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, estimates of comorbidity between PTSD and some types of TBI, including combat-related TBI, are as high as 73% (Hoge et al, 2008;Taylor et al, 2012). Moreover, epilepsy is often found to occur with diseases, including autism/fragile X (Berry-Kravis et al, 2010;Khetrapal, 2010), schizophrenia (Kandratavicius et al, 2012), AD (Palop et al, 2007;Chan et al, 2015), and anxiety disorders (Trimble and Van Elst, 2003;Vazquez and Devinsky, 2003). Indeed, many of these disorders have comorbidities, and often these comorbidities involve deficiencies within the BLA GABAergic system.…”
Section: Discussionmentioning
confidence: 99%
“…For example, estimates of comorbidity between PTSD and some types of TBI, including combat-related TBI, are as high as 73% (Hoge et al, 2008;Taylor et al, 2012). Moreover, epilepsy is often found to occur with diseases, including autism/fragile X (Berry-Kravis et al, 2010;Khetrapal, 2010), schizophrenia (Kandratavicius et al, 2012), AD (Palop et al, 2007;Chan et al, 2015), and anxiety disorders (Trimble and Van Elst, 2003;Vazquez and Devinsky, 2003). Indeed, many of these disorders have comorbidities, and often these comorbidities involve deficiencies within the BLA GABAergic system.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review of ASD focusing on comorbidity revealed few articles that were based on population studies. 3,4 Studies of comorbidity with ASD focus primarily on other psychiatric disorders, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] neurologic disorders, [24][25][26][27][28] or congenital disorders. [29][30][31][32] Few studies focused on physical disorders, [33][34][35] and fewer still focused on adults.…”
Section: Introductionmentioning
confidence: 99%